2021
DOI: 10.1155/2021/6622809
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Incremental Yield of the Chest X-Ray in Screening for Tuberculosis in Uganda: A Cross-Sectional Study

Abstract: The WHO END TB strategy requires ≥90% case detection to combat tuberculosis (TB). Increased TB case detection requires a more sensitive and specific screening tool. Currently, the symptoms recommended for screening TB have been found to be suboptimal since up to 44% of individuals with TB are asymptomatic. The chest X-ray (CXR) as a screening tool for pulmonary TB was evaluated in this study, as well as its incremental yield in TB diagnosis using a cross-sectional study involving secondary analysis of data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Like prior research, in this study, CXR screening increased TB case detection, reducing TB incidence and mortality [5,27]. However, CXR screening incurs high costs [11,27,30]. Total costs for CXR screening across the general population were more than 10 times higher than those for national TBSS screening in this study, aligning with findings in a study in Vietnam [31].…”
Section: Principal Findingssupporting
confidence: 85%
See 2 more Smart Citations
“…Like prior research, in this study, CXR screening increased TB case detection, reducing TB incidence and mortality [5,27]. However, CXR screening incurs high costs [11,27,30]. Total costs for CXR screening across the general population were more than 10 times higher than those for national TBSS screening in this study, aligning with findings in a study in Vietnam [31].…”
Section: Principal Findingssupporting
confidence: 85%
“…Like prior research, in this study, CXR screening increased TB case detection, reducing TB incidence and mortality [5,27]. However, CXR screening incurs high costs [11,27,30].…”
Section: Principal Findingssupporting
confidence: 64%
See 1 more Smart Citation
“… 35 The yield of TB diagnoses increased by 38% as a result of screening methodologies that include chest X-ray in addition to symptoms. 13 According to the EXIT-TB project done in East Africa, the use of chest X-ray services for TB increased TB case detection and reduced delays in TB care. 36 The Global Plan recommends that, at minimum, 95% of people developing TB each year need to be diagnosed and treated, and that no one should be left behind.…”
Section: Discussionmentioning
confidence: 99%
“… 12 A study done in Uganda reported chest X-ray screening for pulmonary TB had 93% sensitivity and 65% specificity, which were higher than the 76% and 31%, respectively, found in symptom screening. 13 The yield of TB diagnosis increased by 38% as a result of screening methodologies that included chest X-rays in addition to symptoms. In Ethiopia, people diagnosed with TB with mild or no symptoms of TB have a better outcome from screening based on chest radiography.…”
Section: Introductionmentioning
confidence: 99%